Study of Ion-Beam-Induced Damage and Luminescence Properties in Terbium-Implanted AlGaN - Park, Ji-Ho; Wakahara, Akihiro; Okada, Hiroshi; Furukawa, Yuzo; Kim, Yong-Tae; Chang, Ho-Jung; Song, Jonghan; Shin, Sangwon; Lee, Jong-Han; Sato, Shin-ichiro; Ohshima, Takeshi (IOP PUBLISHING LTD, 2010)
Terbium (Tb) ions were implanted into Al0.35Ga0.65N epitaxial layers at room temperature to investigate ion-beam-induced damage and luminescence properties at various doses of 1 x 10(12)-2.8 x 10(16) Tb/cm(2). Rutherford backscattering spectrometry/channeling (RBS/channeling) reveals that ion-beam-induced damage level steeply increases and that the damage cannot be fully suppressed even after rapid thermal annealing at 1100 degrees C, when the dose exceeds 5 x 10(14) Tb/cm(2). However, cawthodoluminescence (CL) intensity related to Tb3+ transitions increased initially and saturated above a dose of 1 x 10(13) Tb/cm(2). Furthermore, transient decay time determined by time-resolved photoluminescence (TRPL) decreased faster and a fast decay component related to the formation of nonradiative Tb-defect complexes became dominant, as Tb ion dose increases. Therefore, the results suggest that Tb-related luminescence properties are much susceptible to defects and nonradiative defects, namely, Tb-defect complexes, are formed under low-dose conditions even at a very low structural defect density. (C) 2010 The Japan Society of Applied Physics
Keywords: EU-DOPED GAN; RARE-EARTH IONS; III-NITRIDES; ALXGA1-XN; EMISSION